Psychometric Properties of the French European Little Developmental Coordination Disorder Questionnaire (LDCDQ-FE): A Pilot Study. (4th May 2023) - Jover, Marianne; Ray-Kaeser, Sylvie; Bertrand, Anne Martine; Memoli, Noémie; Albaret, Jean Michel; Rihtman, Tanya
Abstract: Aims: The Little Developmental Coordination Disorder Questionnaire (LDCDQ) is a parental questionnaire designed to identify preschool children at risk of Developmental Coordination Disorder (DCD). This study aimed to translate and cross-culturally adapt the LDCDQ for French European informants (Little Developmental Coordination Disorder Questionnaire-French European [LDCDQ-FE]) and to undertake a pilot examination of its psychometric properties on a French sample. Methods: A thorough process of cultural adaptation was completed. The psychometric properties were examined with a sample of 154 French children aged to 5y11m (control = 121; clinically referred = 33). A sub-group of 34 children was assessed using the MABC-2 to measure convergent validity. Results: Principal component analysis demonstrated a four-component structure, accounting for 67.5% of the variance. Internal consistency was acceptable to good ( α  = 0.74–0.89). Significant correlation between the LDCDQ-FE and the MABC-2 total scores showed convergent validity. Discriminant validity was supported by significant score differences between the clinically referred and a matched control sub-group. Using ROC curves, a cutoff of 67 was proposed for a sensitivity of 81.3% and a specificity of 77.8%. Conclusions: Results show initial evidence of the psychometric properties of the LDCDQ-FE and are encouraging of its use to identify young preschoolers at risk for DCD. In future studies, the test-retest reliability should be investigated, and study sample sizes expanded.